2021
DOI: 10.1016/j.omto.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Systematic profiling of ferroptosis gene signatures predicts prognostic factors in esophageal squamous cell carcinoma

Abstract: We developed a predictive model associated with ferroptosis to provide a more comprehensive view of esophageal squamous cell carcinoma (ESCC) immunotherapy. Gene expression data and corresponding clinical outcomes were obtained from the GEO and The Cancer Genome Atlas (TCGA) databases, and a ferroptosis-related gene set was obtained from the FerrDb database. We identified 45 ferroptosis-related genes that were differentially expressed, including enrichment in genes involved in the immune system process. We est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
4
36
1
Order By: Relevance
“…We further demonstrated that the expression of GPX4 in tumorous specimens from esophageal cancer patients is correlated with a poor prognosis ( Figure 5 A,B). Our findings also support recent studies that identified ferroptosis-related gene signatures, which can be used to predict the prognosis and immunological responses of esophageal squamous cell carcinoma and other cancers [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…We further demonstrated that the expression of GPX4 in tumorous specimens from esophageal cancer patients is correlated with a poor prognosis ( Figure 5 A,B). Our findings also support recent studies that identified ferroptosis-related gene signatures, which can be used to predict the prognosis and immunological responses of esophageal squamous cell carcinoma and other cancers [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Since extensive crossover between immunotherapy and non-apoptotic RCD mechanisms has been detected, non-apoptotic cancer cell death accompanied by immunomodulation is considered an exceedingly promising strategy for cancer treatment [ 28 ]. Ferroptosis, a neoteric form of RCD with unique biological and morphological features, has been shown to interact with the tumor immune response and can influence immunotherapeutic efficacy on the one hand [ 8 ], and in turn is regulated by immune cells on the other [ 7 ]. In the present study, based on ferroptosis-related genes in STS, we identified potential ICGs including PDCD1, CTLA4, TIGIT, IDO1 and CD27, which might serve as important targets for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ferroptosis has exhibited great potential in the treatment of cancer and has gained widespread attention in STS as well [ 6 ]. Recent studies have revealed that ferroptosis and tumor immunity can be mutually regulated [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that KIRC is closely related to von Hippel-Lindau (VHL) gene changes ( Zhang et al, 2018 ; Zhang et al, 2020 ). In addition, ferroptosis-related genes, some miRNAs, and pathways also participate in regulating the process of KIRC regulation ( Lu et al, 2021 ; Zhang et al, 2021 ). Autophagy plays a vital role in cell physiology, including adaptation to metabolic stress, removal of dangerous substances, renewal during differentiation and development, and prevention of genome damage ( Levine and Kroemer, 2008 ; Levine and Kroemer, 2019 ).…”
Section: Instructionmentioning
confidence: 99%